Teaching Adaptations
X, 195 p.
Keywords: Teaching Adaptations addresses the challenges and appeal of teaching popular fiction and culture, video games and new media content, which serve to enrich the curriculum, as well as exploit the changing methods by which English students read and consume literary and screen texts.